Climate variability and climate change: Impacts on Kenyan agriculture - Herrero, Mario; Ringler, Claudia; van de Steeg, Jeannette; Zhu, Tingju; Bryan, Elizabeth; Omolo, Abisalom; Koo, Jawoo; Notenbaert, An Maria Omer; Thornton, Philip K. (International Food Policy Research Institute, 2010)
Characteristic of much of Sub-Saharan Africa, Kenya is highly vulnerable to climate change. The country and greater region already experience high temperatures and relatively low but highly variable precipitation while their economies remain dependent on rainfed agriculture. Adoption of modern technology is low; poverty remains widespread; and infrastructure under-developed. In order to devise adaptation strategies for smallholders in Kenya, researchers need to assess the impact of climate change and variability on the agriculture sector and economy. This project note is based on a report that gives an overview and analysis of climate variability, climate change, and their respective agricultural impacts.